Light-Driven Reactivity of Alkynes with Carbenes Derived from Diazo Compounds. - Yamini, Pokhriyal; Abhishek, Pandey; Dongari, Yadagiri (Synthesis)
Here, we comprehensively summarize the reactivity of alkynes with carbenes derived from diazo compounds and related precursors in the presence of visible light. The alkynes' rich reactivity is demonstrated through various reactions, including cyclopropenation, C-H insertion, annulation, synthesis of heterocyclic compounds via cycloaddition, and synthesis of bistrifluoromethylated trienes and tetrasubstituted allenes. These reactions are discussed along with their mechanisms, which occur under visible light with/without photo-redox catalysts or additives.